Non-cash transactions and the money supply - Rahmadani, Shinta Ainur; Pratama, Aprika Wanti; Yunita, Nurma; Panorama, Maya (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2023)
This study examines the impact of non-cash transactions and electronic money (emoney) on the amount of money in circulation (M1) in Indonesia. Utilizing a quantitative approach and an associative research design, the analysis draws on secondary data from monthly time series publications by Bank Indonesia and the Central Statistics Agency, spanning from 2019 to 2021. The independent variables include the nominal values of debit card transactions (X1), credit card transactions (X2), and e-money transactions (X3), all measured in billions of rupiah. The regression results reveal no immediate linear effect of debit card transactions on the money supply, while credit card transactions show a slight negative impact. In contrast, emoney transactions exhibit a significant positive relationship with the money supply, indicating their substantial role in expanding monetary aggregates. These findings offer insights into the interplay between different transaction types and their influence on the money supply, providing a basis for policymakers and financial analysts to develop strategies for managing and regulating monetary dynamics effectively. Further research is recommended to explore the mechanisms driving these relationships and their broader implications for monetary policy and financial stability.